Gastric cancer: frequency and trends - Lunet,Nuno (2006)
A continued international decline in gastric cancer mortality is one of the most remarkable events in cancer epidemiology. This "unplanned triumph", however, is characterized by geographical differences in cancer frequency and trends, both between and within countries. The declining incidence of gastric carcinoma could be explained primarily by the decrease in the relative number of intestinal type cases, and the cancers of the cardia show increasing or stable trends. The understanding of the site and histological type specific trends in each region, overcoming the methodological difficulties and the gaps in our knowledge of cancer aetiology, are essential to predict the future burden of gastric cancer.